Pengaruh Pelatihan, Budaya Organisasi Islam dan Kompensasi Terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening di PT Daya Surya Sejahtera Ponorogo - Eva Rosyidah; Ely Masykuroh; Shinta Maharani (Institut Agama Islam Negeri Ponorogo, 2025)
This study aims to analyze the influence of training, Islamic organizational culture, and compensation on employee performance with work motivation as an intervening variable at PT. Daya Surya Sejahtera Ponorogo. The research employs a quantitative approach to examine the relationships among variables empirically. Data were collected through interviews and questionnaires involving 156 respondents, and analyzed using simple linear regression, multiple linear regression, and path analysis. The results show that the research findings indicate that: (1) training has no significant effect on employee performance (Sig. = 0.209); (2) Islamic organizational culture also has no significant effect on performance (Sig. = 0.454); and (3) compensation has a significant effect on employee performance (Sig. = 0.035). Furthermore, (4) training has a positive and significant effect on work motivation (Sig. = 0.000); (5) Islamic organizational culture has a positive and significant effect on work motivation (Sig. = 0.000); and (6) compensation also has a positive and significant effect on work motivation (Sig. = 0.000). In addition, (7) work motivation significantly affects employee performance (Sig. = 0.000). Path analysis results show that (8) training, (9) Islamic organizational culture, and (10) compensation have a significant effect on employee performance through work motivation as an intervening variable. Specifically, the direct effect of Islamic organizational culture on performance is not significant (Sig. = 0.128), but the indirect effect through motivation as a mediator is significant (Sig. = 0.000). The total effect of compensation on employee performance is 0.744, with the most significant contribution coming from the indirect effect through work motivation, amounting to 0.489. Based on these findings, it can be concluded that work motivation is a crucial mediating factor that strengthens the influence of training, Islamic organizational culture, and compensation on improving employee performance at PT. Daya Surya Sejahtera.